Delayed Effects of Acute Radiation Exposure in a Murine Model of the H-ARS: Multiple-Organ Injury Consequent to <10 Gy Total Body Irradiation. Issue 5 (November 2015) - Unthank, Joseph L.; Miller, Steven J.; Quickery, Ariel K.; Ferguson, Ethan L.; Wang, Meijing; Sampson, Carol H.; Chua, Hui Lin; DiStasi, Matthew R.; Feng, Hailin; Fisher, Alexa; Katz, Barry P.; Plett, P. Artur; et al.
Abstract : Abstract: The threat of radiation exposure from warfare or radiation accidents raises the need for appropriate animal models to study the acute and chronic effects of high dose rate radiation exposure. The goal of this study was to assess the late development of fibrosis in multiple organs (kidney, heart, and lung) in survivors of the C57BL/6 mouse model of the hematopoietic-acute radiation syndrome (H-ARS). Separate groups of mice for histological and functional studies were exposed to a single uniform total body dose between 8.53 and 8.72 Gy of gamma radiation from a 137 Cs radiation source and studied 1–21 mo later. Blood urea nitrogen levels were elevated significantly in the irradiated mice at 9 and 21 mo (from ∼22 to 34 ± 3.8 and 69 ± 6.0 mg dL −1, p < 0.01 vs. non-irradiated controls) and correlated with glomerosclerosis (29 ± 1.8% vs. 64 ± 9.7% of total glomeruli, p < 0.01 vs. non-irradiated controls). Glomerular tubularization and hypertrophy and tubular atrophy were also observed at 21 mo post-total body irradiation (TBI). An increase in interstitial, perivascular, pericardial and peribronchial fibrosis/collagen deposition was observed from ∼9–21 mo post-TBI in kidney, heart, and lung of irradiated mice relative to age-matched controls. Echocardiography suggested decreased ventricular volumes with a compensatory increase in the left ventricular ejection fraction. The results indicate that significant delayed effects of acute radiation exposure occur in kidney, heart, and lung in survivors of the murine H-ARS TBI model, which mirrors pathology detected in larger species and humans at higher radiation doses focused on specific organs. Abstract : Supplemental digital content is available in the text.